Detection of microstructural white matter alterations in functional gastrointestinal disorders assessed by diffusion kurtosis imaging. Issue 5 (12th June 2020) - Chiba, Toshimi; Ito, Kenji; Mori, Futoshi; Sasaki, Makoto; Matsumoto, Takayuki
Abstract: Background and Aim: We evaluated whether diffusion kurtosis and tensor imaging (DKI/DTI) could reveal microstructural alterations in the brains of patients with functional gastrointestinal disorders (FGIDs), and whether imaging findings were correlated with health‐related quality of life (HRQOL). Methods: Twelve patients with FGIDs fulfilling the Rome IV criteria, and seven healthy controls were examined using a 3 T magnetic resonance (MR) scanner. Tract‐based spatial statistics and regions of interest analyses were performed to compare the mean kurtosis (MK), fractional anisotropy (FA), and mean diffusivity (MD) between patients with FGIDs versus controls. HRQOL was assessed in patients with FGIDs using the eight‐item short form of the Medical Outcome Study Questionnaire (SF‐8) and the Gastrointestinal Symptom Rating Scale. Results: Patients with FGIDs had extensive, widespread regions of reduced MD in the white matter in comparison with healthy controls, whereas no significant differences were observed in MK and FA. No significant differences in deep gray matter for the MK, FA, and MD values were observed between patients with FGIDs and controls. In patients with FGIDs, the FA values in the globus pallidus had a significant and negative correlation with SF‐8 (a mental component summary) ( r = −0.797, P = 0.01 uncorrected for multiple comparisons). Conclusions: DKI/DTI can help identify microstructural white matter alterations in patients with FGIDs. The FA values in the globus pallidus may be useful for a severity assessment of FGIDs. Abstract : We evaluated whether DKI/DTI could reveal microstructural alterations in the brains of patients withFGIDs, and if imaging findings were correlated with HRQOL. Patients with FGIDs had extensive, widespread regions of reduced MD in the white matter in comparison with healthy controls. In FGIDs, the FA values in the globus pallidus had a significant and negative correlation with SF‐8 (a mental component summary). The FA values in the globus pallidus may be useful for a severity assessment of FGIDs.